Implementasi Pelayanan Publik di Provinsi Riau dan di Provinsi Jakarta Berdasarkan UU No. 25 Tahun 2009 - Henny Andriani; Charles Simabura (Faculty of Law, Andalas University, 2017)
The implementation of the act of number 25 years 2009 about the public services in an effort to create the principle of good governance ( good governance ) in the province of Riau and Jakarta west important because of anything services for the community of course there has been a the command of implementation , procedures and authority so that the recipient the service will be satisfied for what he received . The implementation of law number 25 years 2009 concerning public services in west sumatra still has not been effective, because of year to year still happens reporting by the community for government agencies, soe, who do not give public services such as delays , abuse, received in exchange for money and services and goods. Constraints that have been faced in the delivery of public among other: the low the quality of public services , public service system not clearly regulated , overlapping authority , the low external supervision from the community , the ineffectiveness of the decentralised system .The efforts being done to deal with the obstacles is besides built supervision external by the community through active provided a report on the ombudsman representatives to Riau and Jakarta , so internal control each agencies needs to be improved the system , if a long considered be unable to improve the quality of public services . The concept of public services ideal is well applied by ombudsman when is supervision public service done with activities investigation initiative , supervision public services , systemic investigation , and the compliance.